A corrosion and tribo-failure analysis of Ni-P-Cu coated mild steel (AISI-1040) at varied copper concentration. (April 2023) - Bhattacharyya, Suparna; Mohanty, Deviprasanna; Kumar, Prashant; Kalyan Das, Suman; Sahoo, Prasanta; Pal, Surya K.; Chakraborty, Sudipto
Highlights: Electroless Ni-P-Cu synthesized on mild steel (AISI-1040) has been used for improving hardness, corrosion and wear resistance properties. The experiments are carried out varying the Cu concentration from 0 g/l to 1.2 g/l resulting with the best optimized result at 1 g/l. Coating morphology, coating thickness, microhardness, corrosion and tribological analysis has been studied and reported. The study can be readily looked upon to be scaled up for industrial shell and tube heat exchanger. Abstract: Mild steel considers the key structural ingredient for manufacturing shell and tube heat exchangers. Corrosion and tribo-failures, on the other hand, is a very crucial industrial problem that can even lead to plant shutdown. The present study thus focuses on utilising Electroless Ni-P-Cu coating on mild steel (AISI-1040) for improving its hardness, corrosion and wear resistance properties. The experiments are carried out varying the Cu concentration at 0 g/l, 0.2 g/l, 0.4 g/l, 0.6 g/l, 0.8 g/l, 1 g/l and 1.2 g/l in the electroless solution bath. The microstructure of the coating has been characterised using SEM and XRD analysis. Coating thickness is determined using FESEM, which has been analysed to be uniform. The corrosion failure analysis of the sample has been studied using Potentiodynamic polarization method. The Tafel and Nyquist Plot showcased a comparative corrosion resistance of the prepared samples. The wear resistance, on the other hand is analysed using a pin-on-disc tribometer depicting the tribo-failure study of the experiment. Both corrosion and tribological analysis proved the sample Ni-P-Cu-1 with a copper concentration 1 g/l to be the best-optimised concentration for the experiment. Moreover, Vickers's microhardness of the coating with respect to mild steel specimen shows an increment of 40–70 %. The study can be readily scaled up by analysing the application on an industrial shell and tube heat exchangers; thus will be helpful for engineers and industrialists of the related field.